2020
DOI: 10.1177/1074248420979235
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing From Oncology to Cardiology: Low-Dose 5-Azacytidine Attenuates Pathological Cardiac Remodeling in Response to Pressure Overload Injury

Abstract: Introduction: Recent evidence suggests that transcriptional reprogramming is involved in the pathogenesis of cardiac remodeling (cardiomyocyte hypertrophy and fibrosis) and the development of heart failure. 5-Azacytidine (5aza), an inhibitor of DNA methylation approved for hematological malignancies, has previously demonstrated beneficial effects on cardiac remodeling in hypertension. The aim of our work was to investigate whether pressure overload is associated with alterations in DNA methylation and if inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…The same results were observed in human cardiac fibroblasts [ 59 ]. Our data also agree with other studies on humans, where it was observed that 5-aza-dC mitigates renal [ 68 , 71 ], cardiac [ 59 , 72 ], and pulmonary [ 60 , 73 , 74 ] fibrosis by reducing hypermethylation of genes associated with fibroblast activation. In another study, it was found that hypermethylation contributes to renal fibrosis and inhibition of DNMTs suppresses chronic unilateral ureteral obstruction-induced renal fibrosis [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The same results were observed in human cardiac fibroblasts [ 59 ]. Our data also agree with other studies on humans, where it was observed that 5-aza-dC mitigates renal [ 68 , 71 ], cardiac [ 59 , 72 ], and pulmonary [ 60 , 73 , 74 ] fibrosis by reducing hypermethylation of genes associated with fibroblast activation. In another study, it was found that hypermethylation contributes to renal fibrosis and inhibition of DNMTs suppresses chronic unilateral ureteral obstruction-induced renal fibrosis [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The supplementation of selenium which is an essential trace element showed obvious cardioprotective effects toward advanced glycation end products (AGEs)-induced heart failure via inhibiting DNMT2-induced DNA methylation of glutathione peroxidase 1 (GPX1) gene promoter in myocytes (165). Moreover, as an inhibitor of DNA methylation, 5-Azacytidine (5aza) has been shown to be effective in attenuating pressure overload-induced myocardial remodeling (166).…”
Section: Dna Methylation Inhibitorsmentioning
confidence: 99%
“…These “epidrugs” would potentially interfere with various epigenetic mechanisms to enhance regenerative cardiomyocytes or inhibit the negative response to cardiac injury [ 97 ]. It has even been suggested that some standard hypertensive drugs could play a major role in indirect epigenetic regulation [ 98 ]. Finally, the reconfiguration of mCpG regions has been suggested as a more individualized approach to cardiovascular-based therapies via epigenetic regulation [ 99 ].…”
Section: Targeting Neonatal Epigenetic Mechanism In Adult Cardiomyocy...mentioning
confidence: 99%